Real-Time Lossless Compression Algorithm for Ultrasound Data Using BL Universal Code - Kim, Jung Hoon; Yeo, Sunmi; Kim, Jong Won; Kim, Kyeongsoon; Song, Tai-Kyong; Yoon, Changhan; Sung, Joohon (Sensors (Basel, Switzerland), 2018)
Software-based ultrasound imaging systems provide high flexibility that allows easy and fast adoption of newly developed algorithms. However, the extremely high data rate required for data transfer from sensors (e.g., transducers) to the ultrasound imaging systems is a major bottleneck in the software-based architecture, especially in the context of real-time imaging. To overcome this limitation, in this paper, we present a Binary cLuster (BL) code, which yields an improved compression ratio compared to the exponential Golomb code. Owing to the real-time encoding/decoding features without overheads, the universal code is a good solution to reduce the data transfer rate for software-based ultrasound imaging. The performance of the proposed method was evaluated using in vitro and in vivo data sets. It was demonstrated that the BL-beta code has a good stable lossless compression performance of 20%~30% while requiring no auxiliary memory or storage.